Espectro trófico de Ilyodon whitei (Pisces: Goodeidae) en el río del Muerto, Morelos, México - Trujillo-Jiménez, Patricia; Díaz-Pardo, Edmundo (Revista de Biología Tropical, 1996)
The diet and feeding habits of llyodon whitei were studied in relation to size, sex and season of the year, by monthly samples taken at Río Muerto, Morelos, México (180 29' 32" N Y 990 43 ' 32" W). Gut contents were analyzed quantitatively by the numeric and frequency of ocurrence methods, revealing variations in relation to size and season of the year. Small individuals mainly fed on animal matter, while larger individuals preferred plants; in the wet season plant matter dominated, as did animal matter in the dry season. General diet justifies clasification of l. whitei as an euryphagous and opportunistic species since it tends either toward an herbivorous or carnivorous diet according to availability.